(untitled) (TAMADDUN NURI JURNALI, 2024)
This article discusses the definition of postmodernism, which accepts the contradictions, the literary theory of postmodernism and the point of view of postmodernism, or the state of postmodernism depends on what nation one lives in or what intellectual tradition one is based on.